Mechanisms and causes of hypomagnesemia. Issue 4 (July 2016) - Agus, Zalman S.
Abstract : Purpose of review: Identification of the mechanisms of magnesium absorption and reabsorption has markedly enhanced our understanding of the causes of hypomagnesemia. Recent findings: New gastrointestinal and renal causes of hypomagnesemia have been recently documented. Summary: The recognition of new mechanisms and causes of magnesium absorption and reabsorption should enhance the ability to monitor patients at risk for hypomagnesemia and improve our ability to mitigate the serious symptoms associated with this disorder.